Empirical design of PID gain scheduler for the control of a nonlinear lag dominant process - Goh, Han Keat. (2008)
The objective of the project is four-fold. Firstly, we studied the extent by which the "PID Gain Scheduler" is able to improve the performance of a "Fixed PID" controller in controlling a nonlinear lag dominant process. Secondly, the effect of different tuning algorithms on the performance of a "Fixed PID" controller is studied. Thirdly, we attempted to establish the existence of a time invariant relationship between set point response and load disturbance response of a "Fixed PID" controller which had initially been tuned for a set point disturbance. Fourthly, an empirical method to optimally design a "PID Gain Scheduler" using time domain specifications is developed.